On solvability of a partial integral equation in the space L_2(Ω ×Ω) - Eshkabilov, Yu. Kh. (Methods of Functional Analysis and Topology, 2008)
In this paper we investigate solvability of a partial integral equation in the space L_2(Ω×Ω), where Ω=[a,b]^ u. We define a determinant for the partial integral equation as a continuous function on Ω and for a continuous kernels of the partial integral equation we give explicit description of the solution.